Plasma rico em plaquetas na cicatrização cutânea de gatos: padronização de técnica e aplicação clínica - Bertoletti, Bianca (2015)
In cats, cutaneous healing presents qualitative and quantitative differences in comparison with another species, that seems predispose them to healing problems. Wounds that heal by first intention present less resistance, rate of contraction and epithelization. In the second intention healing, the inflammatory phase is bland and the proliferative phase has slow appearing and progression. Considering these aspects, it becomes important to search ways to promote and conduce cutaneous wound healing in cats. The aims of this study were standardize a technique to obtain autologous platelet-rich plasma (PRP) in cats and evaluate your effect on cutaneous healing of experimentally produced wounds in this species. The experiment was developed in two stages: three manual protocols to produce autologous platelet-rich plasma in cats were compared in the first stage. Fifteen adult healthy indoor cats, randomly divided into three groups, were utilized. Five samples of 4.5 ml of jugular blood were collect, with a vacuum system, sequentially in citrated tubes from each cat. The samples were processed using double centrifugation protocols (P): P1 (113g 10 minutes; 652g 5 minutes); P2 (400g 10 minutes; 800g 10 minutes); P3 (400g 10 minutes; 600g 10 minutes). Platelet concentration obtained in PRP obtained in different protocols and the ratio of PRP and platelet counts were compared by t-test. The feasibility of the collect method to the species and ease of execution of techniques was evaluated too. In the second stage, ten healthy adult indoor cats were used. In each animal were surgically produced four circular skin defects, with a diameter of 1 cm, on left and right sides of trunk dorsal midline. The lesions on one side were treated with fluid PRP, obtained of animal itself, according to the best protocol defined in the first stage of the experiment. The control defects in the opposite side were filled with NaCl 0,9% sterile solution. Three observers evaluated the wounds, every three days, for 28 days. The presence of crusts, pain, swelling, exudate, granulation tissue and the color were considered. The results were statistically evaluated by Mann-Whitney rank test. The area of each lesion was analyzed by morphometry every seven days and the data compared by t-test. Skin fragments with normal and scar tissue, from two more cranial lesions (treated and control), were obtained weekly. The fragments were stained with hematoxylin-eosin (HE) and Masson's trichrome, and qualitatively evaluated for the presence of crust, ulcer, acanthosis, fibroplasia, collagen deposition and neovascularization. These data were analyzed using the Mann-Whitney rank test. The collect method was satisfactory and simplified the procedure. Two techniques (P2 and P3) were effective to produce PRP, yielding concentrations higher than 1x106 platelets.μL-1. The P3 protocol was statistically higher in capacity increase, and was selected for use in experimental wounds. In the second stage, the techniques for blood collection, and the selected protocol, were satisfactory. The use of PRP in liquid form, deposited directly on the lesion, made it easy to use. Clinically, there was a statistically significant difference (p = 0.025) and higher exudation in wounds treated to three days. In morphometric analysis we noticed a greater contraction in wounds treated with PRP, especially of the first seven days (p = <0.001). Histopathological evaluation was not significant in any compared parameters. Therefore, it is concluded that the sampling method is efficient and P2 and P3 protocols can be considered feasible to obtain PRP from cats. The protocol P3 was superior in the platelet concentration ability, producing a better quality PRP. Activation of PRP liquid by tissue injury is possible. The increased exudation suggests enhancement of the inflammatory process in treated wounds. Therapeutic use of liquid PRP improves contraction capacity on experimental wounds in cats, despite the absence of histological evidence by way the evaluation adopted.